Looking for Pythagoras (pp. 65--70) - Schulte, Caroline (Ohio Journal of School Mathematics, 2020)
The author discusses the process and revision of a lesson implemented in a 7th-grade classroom. Students explored triangles and the areas associated with their side lengths in order to discover the Pythagorean theorem. The lesson was then revised to use tools such as patty paper and GeoGebra software.